Carbon footprint analysis of chemical enhanced primary treatment and sludge incineration for sewage treatment in Hong Kong. (1st November 2020) - Zhuang, Huichuan; Guan, Jianyu; Leu, Shao-Yuan; Wang, Ying; Wang, Huaimin
Abstract: The potential of greenhouse gas (GHG) emissions from sewage management of metropolis is a critical concern in the water-energy-nexus. With limited space and costly labor, the chemical enhanced primary treatment (CEPT) process associated with sludge incineration was developed in Hong Kong for sewage and sludge treatment, respectively. However, the potential impacts of direct discharge of CEPT effluent in the receiving waterbody, i.e., the possible GHGs emissions after the expected increase of total wastewater loads, have never been addressed. Using Hong Kong as a research platform, this study developed nine scenarios with different wastewater and sludge treatment processes to study the energy profiles and direct/indirect carbon emissions. The impacts from different emission sources to global warming were evaluated. Two of the scenarios represent the ongoing Stonecutters Island Sewage Treatment Works (SCISTW) and Shatin Sewage Treatment Works (STSTW), of which CEPT and activated sludge process (ASP) were in operation, respectively. The results showed that the energy efficiency of the SCISTW (0.065 kW h·m −3 wastewater treated) was 71% lower than that of the STSTW (0.224 kW h·m −3 ), but the GHG emission was higher in the CEPT plant (0.625 kg CO2 -e·m −3 ) than the ASP plant (0.408 kg CO2 -e·m −3 ). The addition of biological process and sludge digester in SCISTW would increase the energy consumption to 0.080 kW h, but reduce the GHG emissions by 70% (to 0.185 kg CO2 -e·m −3 ). Sending the sludge cake to incineration would eliminate 64% of the GHG emissions from STSTW. Applying CEPT in the system may further reduce GHG emissions due to changed sludge combination, which may also be beneficial to energy recovery. Highlights: Carbon neutral practice can be challenging in sewage treatment of metropolis. Direct discharge of CEPT effluent increases carbon emission by 0.502 kg CO2 -e·m −3 . Replacing landfills with incinerator reduces CH4 emission by 0.105 kg CO2 -e·m −3 . Combined process showed a 70% carbon reduction compared with current practices.